Pengelolaan Keuangan Masjid Di Jabodetabek - Rini Rini (Jurnal Akuntansi dan Keuangan Islam, 2018)
The purpose of this research is to describe the financial management of mosques in Jabodetabek (Jakarta, Bogor, Tangerang and Bekasi). Financial management in terms of the preparation of financial statements, types of financial statements made, media publication of financial statement, bank accounts owned by mosques, types of sources of mosque fund receipts and audits of mosque financial statements. This research uses quota sampling. There are 185 districts in the Jabodetabek area, and the sample of mosques from 40 sub-districts is determined. Samples were taken randomly as many as 3 mosques per district. Data sources come from interviews with mosque finance managers. Number of sample in this research is 116 mosques. The results showed that most of the mosques already had financial statements. The types of financial statements that are made mostly are only cash reports. Publication of financial statement to worshipers, mostly by announcing at Friday prayers. The account owned by the mosque is mostly in the name of the manager. Mosque reception mainly comes from infaq and waqf of pilgrims. Only a small number of mosques have been audited for their financial statements